Tourism ecolabelling : certification and promotion of sustainable management (CABI, 2001)
The use of ecolabels and certification schemes in the tourist industry is reviewed. Over 70 schemes are described, from the developed countries of the Northern Hemisphere and Australia. Ways for widening the applicability and hence validity of these ecolables are suggested in conclusion. The book is divided into an introductory section (Chapters 1-2) and four parts. Part 1 discusses the contexts of tourism ecolabels (Chapters 3-6). Part 2 presents the practical approach of ecolabels development (Chapters 7-12). Part 3 reviews the recent changes in ecolabels and their current developments (Chapters 13-15). A strategic analysis of tourism ecolabels is presented in Chapter 16. Part 4 presents a directory of current ecolabels. Ecolabels are viewed as marketing tools that promote good environmental performance. The book is indexed.